Farmland Investments in Tanzania: a Local Perspective on the Political Economy of Agri-food Projects - Bélair, Joanny (Université d'Ottawa / University of Ottawa, 2019)
Using Tanzania as a case-study, this dissertation approaches the land grab issue in Tanzania with the following two main research question: How are new farmland investments shaping political dynamics and actors’ interactions in Tanzania? And, how actors’ interactions between and within levels of governance influence farmland investments’ outcomes at the local level? I tackle these questions by proposing an original theoretical framework which is based on two main assertions. First, local outcomes associated with farmland investments in Tanzania result from actors’ interactions. Second, these interactions are shaped by the interplay between three main elements: contingencies (C), actors’ agency (A), and structure (S). I use the acronym CAS to refer to these three elements. CAS, by combining various theoretical insights, is analytically productive because it furthers our understanding of what shapes relations among actors, and accounts for how their interactions change in time and space. It contributes significantly to the literature on land grabbing by proposing a unified analytical tool that builds up on the relational perspective that has been proposed by different scholars. In addition, CAS allows researchers to overcome misleading categorisations and to question dominant narratives that have been associated with the land grabbing literature. This dissertation is divided into 9 chapters. After the usual literature review (Chapter 1), theoretical framework (Chapter 2) and method (Chapter 3) chapters, Chapter 4 gets into the crux of the matter by first briefly presents Tanzania’s historical trajectory, with a specific focus on land policies in order to introduce this thesis’s empirical chapters, and to situate the reader in regards to Tanzania politics. Chapter 5 analysed land policies and related politics at the national level. It highlighted that actors’ interactions in relation to new farmland investments participate to the process of state formation. Chapter 6 and Chapter 7 both adopted a local perspective to capture the impacts associated with new farmland investments in district political arenas. More specifically, chapter 6 highlighted the importance of not overstating the authority of the central state, rather insisting on the key role played by intermediaries in Rufiji district. Chapter 7, seeking to capture how a specific investment has restructured the local political agrarian economy in Missenyi district, argued that Kagera Sugar safeguards its operational profitability by creating locally mediated market relations. It led to the emergence of new local patrons who used their position to benefit and foster their own material interests at villagers’ expense. Chapter 8 adopted a micro perspective, examining the political dynamics associated with investors-related land conflicts in a village in Missenyi district. I compared and explained why actors’ interactions are different even in the same institutional context, highlighting that the same local context may produce different CASs. In sum, this dissertation’s main findings are as follow. First, investments’ local impacts are contingent on investments’ terms of inclusion and exclusion that are constantly being negotiated between numerous actors. Second, although all actors exert their agency, their very capacity to negotiate and shape the social structure is partly influenced by structural constraints themselves. Third, it is interesting to note that specific local actors—and not necessarily the most powerful—such as district officials win almost every time, at least more than all the others. Although their place in the institutional architecture is decisive, it also shows that their capacity and ability to exert their agency is crucial: these district officials may have known better than others how to play their cards in the new Tanzanian farmland investment game. Fourth, even though processes through which new farmland investments affect the local political economy vary according to structural components (historical and institutional legacies), in both districts, the associated local outcomes were very similar. There are few exceptions, but the general trend in Tanzania is that most of the benefits associated with new farmland investments, the commodification of land and the increase of capital flows, are captured by government officials and political elites.
Keywords: Land grabbing; Political relations; Tanzania; Investment; State formation; Clientelistic; Infrastructural; Autochthony